Performance Analysis of Point-to-Point LoRa End Device Communication - Triwidyastuti, Yosefine (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2019)
LoRa is an emerging communication technology that can be used in any field. Many types of research have analyzed LoRa network using a gateway and several end devices to many monitoring applications. However, the communication performance between LoRa end devices only has not been evaluated. This research tested a LoRa communication between two end devices in a point-to-point topology. From the experiment results with various payload lengths, the optimum payload is only 48 bytes with the default module configuration. Longer payload resulted in a decreased performance. Thus, this research implemented a waiting protocol that can increase the Packet Reception Ratio of 100-byte payload from 49.87% to 97.52%.